Gender and Language: Analyzing Communication Styles in Argumentative Writing - Nugroho, Mario; Suseno, Igantius Gatot (Journal of Communication and Public Relations, 2025)
This study investigates gender-based differences in communication styles within argumentative writing, focusing on syntactic elements like pronouns and noun modifiers, as well as pragmatic aspects such as argumentation strategies. Using a mixed-method approach, data were collected from 30 students in the 2011 cohort of an English Department in Indonesia, evenly split between male and female participants. Quantitative analysis revealed that men utilized personal pronouns more frequently, emphasizing individuality and logical reasoning, whereas women employed noun modifiers more often, showcasing precision and elaboration. Qualitative findings highlighted that men’s arguments leaned towards directness and assertiveness, often grounded in bold claims, while women’s arguments demonstrated greater coherence and emotional engagement, reflecting inclusivity and relational focus. These stylistic variations align with broader sociolinguistic patterns tied to gender. The study underscores the importance of understanding these differences to improve teaching methods and encourage the balanced development of argumentative writing skills across genders. The findings contribute to the growing body of research on gendered communication in second-language contexts, offering insights for educators and linguists aiming to address linguistic and cultural nuances in academic writing.